Green urban transition: interdisciplinary insights on green façades design in hot climates as one of crucial strategies for low-carbon development - Katarzyna Chojnacka; Barbara Widera; Marcel Macarulla; Anastasios Drougkas; Andreu Balastegui; Els Van de moortel; Cansu Iraz Seyrek Şık; Kajetan Sadowski; Joana Fernandes; Ricardo Gomes; Paulo Ferrão (Clean Technologies and Environmental Policy, 2025)
The purpose of this study is to present interdisciplinary insights on vertical green systems (VGS) design in hot climate zones. The approach to the VGS design proposed in this article combines architectural design, structural systems, green building and township development with sustainable urban farming, circularity, waste and water management. On the basis of in-depth study on green façade performance in hot climates, the authors identified methods derived from various fields of science which, when correctly combined, enable effective protection of plants against excessive solar radiation. The main finding of the research is the identification of the most effective combination of methods supporting healthy growth of the VGS. This set of solutions includes orientation of the façade to cardinal directions correlated with appropriate plants selection, shading strategies, such as passive and kinetic shields and organic fertilizers supporting plants’ resilience. The authors presented key challenges and opportunities of VGS application and discussed their role in the decarbonization process of the building sector. The multidisciplinary analysis of the state of knowledge highlighted areas that require further investigation, such as the practical implementation of proposed strategies and their effectiveness in real-world scenarios. Graphical abstract

Experimental investigation on the shear behaviour of the brickwork-backfill interface in masonry arch bridges - Bowen Liu; Anastasios Drougkas; Vasilis Sarhosis; Colin C. Smith; Matthew Gilbert (Engineering Structures, 2023)